Transformasi Layanan Perpustakaan Menuju Smart Library: Kajian Inovasi Teknologi dan Adopsi Pengguna - Faras Puji Azizah; Nasrul Makdis; Dian Maisaroh (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Modern libraries are undergoing a significant transformation along with the development of digital technology. This research aims to examine the role of technological innovation in transforming conventional library service systems into digital-based services that are more efficient and adaptive to the needs of modern society. The method used is descriptive qualitative through a literature review that collects data from various scientific sources. The analysis focused on the application of technologies such as artificial intelligence (AI), Internet of Things (IoT), and cloud computing, and their impact on collection management, information access, and user interaction. The results of the study show that technology provides various benefits, such as increased operational efficiency, easier access to information, and more personalized services. However, the application of technology also faces challenges, such as limited infrastructure, data security, and digital skills. To optimize its use, cross-sector collaboration, librarian training, and policies that support digital inclusion are needed. This research confirms that libraries that are adaptive to technology will be better able to meet the needs of people in the information age and act as centers of inclusive and sustainable digital literacy.